Comparative effects of acute-methionine loading on the plasma sulfur-amino acids in NAC-supplemented HIV+ patients and healthy controls - Burini, Roberto Carlos [UNESP]; Borges-Santos, Maria Doroteia [UNESP]; Moreto, Fernando [UNESP]; Yu, Yong- Ming (Springer Nature, 2018)
In this study, an acute overloading of methionine (MetLo) was used to investigate the trassulfuration pathway response comparing healthy controls and HIV+ patients under their usual diet and dietary N-acetyl-l-cysteine (NAC) supplementation. MetLo (0.1 g Met/kg mass weight) was given after overnight fasting to 20 non-HIV+ control subjects (Co) and 12 HIV+ HAART-treated patients. Blood samples were taken before and after the MetLo in two different 7-day dietary situations, with NAC (1 g/day) or with their usual diet (UD). The amino acids (Met, Hcy, Cys, Tau, Ser, Glu and Gln) and GSH were determined by HPLC and their inflow rate into circulation (plasma) was estimated by the area under the curve (AUC). Under UD, the HIV+ had lower plasma GSH and amino acids (excepting Hcy) and higher oxidative stress (GSSG/GSH ratio), similar remethylation (RM: Me/Hcy + Ser ratio), transmethylation (TM; Hcy/Met ratio) and glutaminogenesis (Glu/Gln ratio), lower transsulfuration (TS: Cys/Hcy + Ser ratio) and Cys/Met ratio and, higher synthetic rates of glutathione (GG: GSH/Cys ratio) and Tau (TG: Tau/Cys ratio). NAC supplementation changed the HIV pattern by increasing RM above control, normalizing plasma Met and TS and, increasing plasma GSH and GG above controls. However, plasma Cys was kept always below controls probably, associatively to its higher consumption in GG (more GSSG than GSH) and TG. The failure of restoring normal Cys by MetLo, in addition to NAC, in HIV+ patients seems to be related to increased flux of Cys into GSH and Tau pathways, probably strengthening the cell-antioxidant capacity against the HIV progression (registered at http://www.clinicaltrials.gov, NCT00910442).
Keywords: Cysteine metabolism; HIV+ patients; Methionine-load test; Thiol redox system